WM-SIM LTE link simulator - Aguayo-Torres, María del Carmen; Blánquez-Casado, Francisco; Delgado-Luque, Isabel-María; Entrambasaguas-Muñoz, José Tomás; Gómez-Paredes, Gerardo; Martín-Vega, Francisco-Javier; Morales-Jiménez, David; Sánchez-Sánchez, Juan Jesús (My University, 2014)
WM-SIM is a standard compliant link-level simulation environment for the 3GPP Long Term Evolution (LTE) technology. The simulator has been developed by the Communications Engineering Research Group at the Universidad de Málaga (Spain). The physical layer implementation for both downlink and uplink is compliant with the 3GPP-LTE Release 8 specifications.
Simulador de enlace LTE WM-SIM
Keywords: Simulación por ordenador; WM-SIM; LTE; Access network; OFDMA; Link simulator